Tourism in Africa: Harnessing Tourism for Growth and Improved Livelihoods - Christie, Iain (World Bank, 2015)
Tourism energizes economies and fuels the economic transformation of countries from Cape Verde to South Africa. Its benefits are clear: it can trigger infrastructure improvements, create good jobs, increase domestic consumption, and diversify exports. It also empowers women, young people, and marginalized populations, contributes to each country?s national image, and stimulates cultural heritage and environmental conservation. What?s more, tourism is a demonstration sector which leads private sector growth through its linkages across other sectors. It has demonstrated resilience over the years and through economic and natural crises.